Muhammadiyah Sebagai Gerakan Islam Berkemajuan - Rudi Haryanto; Ernawati .; M. Amin (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
This study aims to analyze the role of Muhammadiyah as a progressive Islamic movement in the context of modern Indonesian society. Muhammadiyah is an Islamic organization founded by Ahmad Dahlan in 1912 with the spirit of tajdid (renewal) and purification of Islamic teachings. The concept of progressive Islam promoted by Muhammadiyah emphasizes the integration of Islamic values, modernity, science, and social progress. This study uses a qualitative approach with library research methods. Data were obtained through analysis of official Muhammadiyah documents, books, and relevant scientific journals. Data analysis techniques were used descriptively and analytically to understand the ideological foundations, forms of the movement, and Muhammadiyah's contributions in the fields of education, health, and social services. The research results show that Muhammadiyah, as a progressive Islamic movement, plays an active role in building a civilization based on the values ​​of monotheism, rationality, and social benefit. Through its charitable endeavors in various fields, Muhammadiyah is able to present a model of Islamic movement that adapts to changing times without abandoning the basic principles of Islamic teachings. Thus, the concept of progressive Islam is relevant as a paradigm for building a religious, modern, and civilized society.